Experimental Investigation on the Effects of Ethanol-Enhanced Steam Injection Remediation in Nitrobenzene-Contaminated Heterogeneous Aquifers - Ruxue Liu; Xinru Yang; Jiayin Xie; Xiaoyu Li; Yongsheng Zhao (Applied Sciences, 2021)
Steam injection is an effective technique for the remediation of aquifers polluted with volatile organic compounds. However, the application of steam injection technology requires a judicious selection of stratum media because the remediation effect of hot steam in heterogeneous layers with low permeability is not suitable. In this study, the removal effect of nitrobenzene in an aquifer was investigated through a series of two-dimensional sandbox experiments with different stratigraphic structures. Four types of alcohols were used during steam injection remediation to enhance the removal effect of nitrobenzene (NB)-contaminated heterogeneous aquifers. The principle of the removal mechanism of alcohol-enhanced organic compounds is that alcohols can reduce the surface tension of the contaminated water, resulting in Marangoni convection, thereby enhancing mass and heat transfer. The addition of alcohol may also reduce the azeotropic temperature of the system and enhance the volatility of organic compounds. The study revealed that all four alcohol types could reduce the surface tension from 72 mN/m to <30 mN/m. However, among these, only ethanol reduced the azeotropic temperature of NB by 15 °C, thereby reducing energy consumption and remediation costs. Therefore, ethanol was selected as an enhancing agent to reduce both surface tension and azeotropic temperature during steam injection. In the 2-D simulation tank, the interface between the low-and high-permeability strata in the layered heterogeneous aquifer had a blocking effect on steam transportation, which in turn caused a poor remediation effect in the upper low-permeability stratum. In the lens heterogeneous aquifer, steam flows around the lens, thereby weakening the remediation effect. After adding ethanol to the low-permeability zone, Marangoni convection was enhanced, which further enhanced the mass and heat transfer. In the layered and lens heterogeneous aquifers, the area affected by steam increased by 13% and 14%, respectively. Moreover, the average concentration of NB was reduced by 51% in layered heterogeneous aquifers and by 58% in low-permeability lenses by ethanol addition. These findings enhance the remediation effect of steam injection in heterogeneous porous media and contribute to improve the remediation efficiency of heterogeneous aquifers by steam injection.